The Effect of Feeding Rules Counseling with Flipcharts on Maternal Knowledge about Overcoming Feeding Difficulties During MP-ASI - Dwi Karina Ariadni; Farida Linda Sari Siregar; Eqlima Elfira; Riska Novita Harahap (Talenta Publisher, 2024)
Feeding dificulties are the frequent problem encountered in infants aged 6-24 months, and one of which is mothers' knowledge in feeding practices. Therefore, providing counseling on feeding rules to mothers is crucial to address the feeding difficulties in infants. Feeding rules are basic eating guidelines designed to train internal eating regulation and provide a structured feeding schedule. The media used is flipchart. This Research is conducted to analyze the effect of counseling on feeding rules using a flipchart on mothers' knowledge in addressing feeding difficulties during complementary feeding (MP-ASI). This is a quantitative Research with a pre-experimental one-group pre-posttest design. A purposive sampling is used to collect data from 69 respondents who meet inclusion criteria: mother with infants aged 6-24 months experiencing feeding difficulties in Lama Village, Hamparan Perak Subdistrict, Deli Serdang Regency. The findings reveal that counseling on feeding rules using a flipchart has a significant effect on mothers' knowledge in addressing feeding difficulties during complementary feeding (MP-ASI), as indicated by the Paired T-Test statistical test with a p-value of 0.000 (<0.05). It is expected that mothers with infants having feeding problems are able to perform feeding rules to address the feeding issues. Furthermore, the results of the Research are expected to serve as an evaluation for healthcare workers to enhance counseling on feeding rules in the community.